A sticky carbohydrate meets a mussel adhesive: Catechol-conjugated levan for hemostatic and wound healing applications. (1st January 2023) - Osman, Asila; Lin, Enhui; Hwang, Dong Soo
Abstract: The stickiest natural polysaccharide, levan, plays a role in metalloproteinase activation, which is an important step involved in the healing of injured tissue. However, levan is easily diluted, washed away, and loses adhesion in wet environments, which limits its biomedical applications. Herein, we demonstrate a strategy for fabricating a levan-based adhesive hydrogel for hemostatic and wound healing applications by conjugating catechol to levan. Prepared hydrogels exhibit significantly improved water solubilities, and adhesion strengths to hydrated porcine skin of up to 42.17 ± 0.24 kPa which is more than three-times that of fibrin glue adhesive. The hydrogels also promote rapid blood clotting and significantly faster healing of rat-skin incisions compared to nontreated samples. In addition, levan-catechol exhibited an immune response close to that of the negative control, which is ascribable to its significantly lower endotoxin level compared to native levan. Overall, levan-catechol hydrogels are promising materials for hemostatic and wound healing applications. Graphical abstract: Unlabelled Image Highlights: Catechol was conjugated to levan to enhance adhesion under wet conditions. Levan catechol hydrogels adhere 3 times more strongly to porcine skin than fibrin glue. Levan catechol hydrogels are highly hemocompatible. Levan catechol hydrogels promote fast blood clotting and high platelet adhesion. Levan catechol hydrogels are highly cytocompatible and promote wound healing in vivo .